SOME REMARKS ON THE DIACHRONY OF FRENCH NEGATION - Roberts, Ian (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
Based on the history of negation in French, this paper proposes a parametrization of how languages may morphologically express the logical structure of negation provided by UG. It is argued that the change of French negation is driven by a general economy principle governing language acquisition, which favors shorter chains over longer ones. It is also claimed that this change correlates with a change in the determiner system which leads negative chains to develop from indefinite chains